CUSTOMER EXPERINCE RELATIONSHIP AGAINST CUSTOMER SATISFACTION IN INDONESIAN MAHKOTA SUKSES (MSI) PRODUCTS AT CIKAMPEK AREA - Santi Irwanti (Universitas Ngudi Waluyo, 2021)
Social and economic changes that continue to occur in the process of developing a country that provides new challenges in the business world of goods and services. Increasing the amount of consumption or consumer needs for goods and services, making many companies use it as an opportunity to increase profits. Many companies take advantage of this opportunity, causing business competition to become increasingly fierce. Steps that must be taken to improve the company's customer experience based on customer satisfaction measurements on MSI products in the Cikampek area. Based on the idea that customer experience can evaluate customer satisfaction. The purpose of this research is to find out which dimension of customer experience is the most dominant toward customer satisfaction and find out the relationship between customer experience and customer satisfaction. This type of research is quantitative research. Data collection in this study uses the method of observation, documentation, and questionnaires. The population in this study was 150 consumers who bought MSI products in the Cikampek area. The sampling technique is simple random sampling using Slovin formula, obtained a sample of 60 respondents with an error level of 1%. Results of data analysis The most dominant dimension of customer experience to customer satisfaction is the sense of dimension, because I feel 88% satisfied or as many as 66 respondents. To determine the relationship between service quality and customer satisfaction. If r count (0.80)> r table (0.214), there is a relationship between customer experience and customer satisfaction in the Cikampek area. Seeing the correlation coefficient of positive (+) 0.80 means that if the customer experience variable goes up, the variable of customer satisfaction will also go up. The relationship between the two variables is very strong. So the results of the correlation coefficient produces 64% and its meaning in the results of these calculations shows that customer experience is related to customer satisfaction on MSI products in Cikampek.Perubahan sosial dan ekonomi yang terus menerus terjadi dalam proses perkembangan suatu negara yang memberikan tantangan baru dalam dunia bisnis baik barang maupun jasa. Meningkatnya jumlah konsumsi atau kebutuhan konsumen akan barang dan jasa, membuat banyak perusahaan memanfaatkannya sebagai peluang untuk meningkatkan profit. Banyaknya perusahaan yang memanfaatkan peluang ini, menyebabkan persaingan bisnis menjadi semakin ketat. Langkah yang harus dilakukan untuk meningkatkan customer experience perusahaan berdasarkan pengukuran kepuasan konsumen pada produk MSI di daerah cikampek. Didasari pada pemikiran bahwa customer experience dapat mengevaluasi kepuasan konsumen. Tujuan penelitian untuk mengetahui dimensi customer experience mana yang paling dominan terhadap kepuasan konsumen dan mengetahui hubungan antara customer experience dengan kepuasan konsumen. Jenis penelitian ini merupakan penelitian kuantitatif. Pengumpulan data dalam penelitian ini menggunakan metode observasi, dokumentasi, dan kuesioner. Populasi dalam penelitian ini adalah 150 konsumen yang membeli produk MSI di daerah cikampek. Teknik pengambilan sampel yaitu Simple random samplingl dengan menggunakan Rumus Slovin, didapat sampel sebanyak 60 responden dengan taraf error 1%. Hasil Analisis data dimensi customer experience yang paling dominan terhadap kepuasan konsumen adalah dimensi panca indra (sense experience), karena saya merasa puas sebesar 88 % atau sebanyak 66 orang responden. Untuk menentukan hubungan antara Customer Experience dengan Kepuasan Konsumen. Jika r hitung (0,80) > r tabel (0,214) maka ada hubungan antara customer experience dengan kepuasan konsumen di daerah cikampek. Melihat nilai koefisien korelasi sebesar positif (+) 0,80 artinya jika variabel customer experience naik maka variabel kepuasan konsumen juga akan naik. Hubungan antara dua variabel tersebut sangat kuat. Jadi hasil koefisien korelasi tersebut menghasilkan 64% dan artinya dalam hasil perhitungan tersebut menunjukkkan bahwa customer experience berhubungan dengan kepuasan konsumen pada produk MSI di daerah cikampek